Pertumbuhan Vegetatif Rumput Raja (Pennisetum purpureophoides) dengan Perlakuan Pupuk Anorganik Dan Organik - Aritonang, Sonria; Rumetor, Sientje Daisy; Yoku, Onesimus (Fakultas Peternakan Universitas Papua, 2020)
This study aims to determine the effect of inorganic fertilizer, organic fertilizer, and the combination of both on the growth of king grass (Pennisetum purpurephoides). The research method was a completely random design with 4 treatments and 5 replications. The research treatments consisted of A (without fertilizer), B (100% inorganic fertilizer), C (100% organic fertilizer), and D (50% inorganic and 50% organic fertilizer). The result of the study shows that inorganic, organic, and its fertilizer combination treatment has a non-significant effect on the height of the plant, the length and width of the leaf, and the length of its segments, while inorganic and organic fertilizer treatment has a significant effect on the stem diameter. The conclusion is that the use of 100 % organic fertilizer has better results for the vegetative growth of king grass (Pennisetum purpurephoides) compared to the use of inorganic fertilizer and its combination.